Medicinal value of camel milk and meat. Issue 1 (1st January 2018) - Abrhaley, Askale; Leta, Samson
ABSTRACT: Camel milk and meat are good source of nutrients for the peoples living especially in the arid and urban areas. Camel milk and meat are unique from other ruminant's milk and meat in terms of composition as well as claimed health effects. Camel milk has low cholesterol, high minerals (sodium, potassium, iron, copper, zinc and magnesium) and high vitamin C when compared with other ruminant milk. Camel milk contains various fatty acids, enzymes and protective proteins. Camel milk has potential therapeutic effects, such as antibacterial, antiviral, antidiabetic, anti-ageing and anticarcinogenic. The medicinal properties of camel milk can be attributed to the presence of protective proteins, which may possibly play a pivotal role for the enhancement of immune defence mechanism. Not only camel milk, but also camel meat in general, is considered a functional food for cures and remedy for many ailments such as seasonal fever, sciatica, shoulder pain, asthma, removing freckles and for improved performance, in many cultures around the world. Therefore, it is important to illustrate the overview of compositions and medicinal values of camel milk and meat.